2021
DOI: 10.1016/j.radi.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The global impact of the COVID-19 pandemic on clinical radiography practice: A systematic literature review and recommendations for future services planning

Abstract: Introduction Worldwide, reports and experiences indicate that there has been extensive re-organisation within diagnostic imaging and radiotherapy departments in response to the COVID-19 pandemic. This was necessary due to changes in workload and working practice guidelines that have evolved during the pandemic. This review provides a comprehensive summary of the global impact of the COVID-19 pandemic on radiography practice, service delivery and workforce wellbeing. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 78 publications
(273 reference statements)
2
30
0
Order By: Relevance
“…The COVID-19 pandemic continues to pose a serious challenge to educational systems worldwide. [1][2][3] The consequent changes within the educational sector, including the transition to online teaching and learning, and restricted movement as a result of the lockdown has impacted clinical radiography education in low resource settings including Ghana. 12 This has widely affected academic, research, and clinical activities in most health training institutions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The COVID-19 pandemic continues to pose a serious challenge to educational systems worldwide. [1][2][3] The consequent changes within the educational sector, including the transition to online teaching and learning, and restricted movement as a result of the lockdown has impacted clinical radiography education in low resource settings including Ghana. 12 This has widely affected academic, research, and clinical activities in most health training institutions.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,15,28 Findings from this study suggested changes in teaching patterns during the pandemic as the regular face-to-face teaching instructions were replaced with online learning, consistent with earlier studies. 1,13,[29][30][31] However most of the respondents, predominantly students, did not find the platform userfriendly. This is because the virtual learning system might not have been part of the traditional face-to-face teaching system before the outbreak.…”
Section: Impact Of the Pandemic On Classroom And Research Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“… 5 Studies of radiographers have identified changes to clinical working patterns, service delivery, personal protective equipment (PPE) shortages and an increase in workplace-related stress amongst practising radiographers. 5 , 6 , 7 Interventional radiographers are a subgroup of frontline highly trained and skilled hospital staff who typically provide imaging to support minimally invasive procedures in highly pressured environments.…”
Section: Introductionmentioning
confidence: 99%